Occurrence and genetic characterization of Listeria spp. in minimally processed vegetables commercialized in Porto Alegre, Brazil - Verdin, Sylvia Elisa Frizzo; Silva, Silvia Regina Pavan da; Pereira, Dariane Castro; Schatkoski, Aline Modelski; Corção, Gertrudes (Acta Scientiae Veterinariae, 2018)
Minimally processed vegetables go through many steps before they are refrigerated, selection, washing, peeling, cutting, disinfection and finally packaging. However, if no care is taken at the origin of the raw materials and in the processing stages, there is a chance of finding pathogenic bacteria, such as Listeria monocytogenes, which are able to grow at low temperatures. The aim of this research was to verify the occurrence of Listeria sp. in minimally processed vegetables sold in Porto Alegre, Brazil, and the genetic relationship among the isolates. Minimally processed salads were sampled monthly from local supermarkets and analyzed by inoculation on Listeria Enrichment Broth and subsequent seeding on two selective media, Palcam and Modified Oxford Agar. The typical colonies were identified to species level and their intergenic region 16S-23S rDNA were amplified in order to verify the genetic variability. Species of Listeria were found in 23 of the 52 processed salad samples analyzed and L. monocytogenes was found in seven. The presence of L. monocytogenes in the samples is a health concern, as these salads are eaten without further treatment by the consumer. The amplification of the intergenic region 16S-23S rDNA, showed a great genetic diversity among the isolates, with 43 different patterns, proving the usefulness of this technique in epidemiologic studies.